History of e-cigarettes use must be part of the dental patient records - Martins, Beatriz Nascimento Figueiredo Lebre; Ribeiro , Ana Carolina Prado; Brandão , Thaís Bianca; Santos-Silva, Alan Roger; Lukose, Kiran; Migliorati , César Augusto (Journal of Oral Diagnosis, 2024)
Introduction: Recent studies have highlighted a significant global increase in e-cigarette use, particularly among young adults. This narrative review targets the important topics related to e-cigarettes that should be introduced to dental professionals. Objective: To review current knowledge of e-cigarettes, the impact on human health and the environment and suggest the incorporation of this information in the dental school curriculum. Study design: Available literature was identified through searches of Medline/PubMed, SCOPUS, EMBASE, reference lists, and books was reviewed. Significant information was collected and analyzed. Results: The review showed that the e-cigarettes are being used by young people who never smoked, and that the device may not be an effective form of tobacco cessation. It revealed the burden of the device on human health and oral cavity, and the environment. It suggested the need to incorporate this information in the dental history forms. Conclusion: Our findings suggest that there is the need to educate dental students on how to take history on patients who use e-cigarettes and how to counsel their patients.